Reforma do Estado no Brasil e o processo de terceirização dos serviços sociais: um estudo na revista Nova Escola - Gibbert, Giane Maria (2008)
This research paper analyzes in what measured the activities developed for the Third Sector, in the dimension of the praxis with conservatives contents of the executors in question, have contributed to accomplish actions theoretician-practical to keep the structure of the capitalist society, in compliance with authorization and financing for the State. The relevancy of the accomplishment of this study has direct relation with the personal and professional necessity in understanding and analyzing this movement and its determination, making possible to contribute with the present and future debate on the social rights. To answer to the research object, we trace as objective generality: to apprehend, through of the contents printed matters of the New School Magazine, edited for the Foundation Victor Civita, the elements that they feed and they strengthen the diffusion of a form to think the field of the rights. For this, we use, as source of empirical research, the bibliographical revision in documents printed matters of the vehicle of communication New School Magazine, in the period understood between February 1998 and December 2007. To mediate the general objective, we establish as objective specific, the identification, in the literature, of different understandings that deal with the citizenship concept and verification of which activities is made possible in the concretion of the relation citizenship/Third Sector, in the New Magazine School. The apprehension and analysis of this movement had evidenced the existence of trends, guided for the neoliberal postulates, in the period after 1990, of retrocession of the social rights and outsourcing in the installment of the social services, now executed for organizations of the Third Sector . Also, it made possible to approach us the mediations that articulate and structuralize the concept of Third Sector , as well as its real course and its use ideological-politician in the treatment of the manifestations of the social matter. Thus, we identify that the Third Sector and innovated speech of the citizenship is new subtle instruments of domination used by the ruling class (bourgeoisie) in order to give continuity in the process of accumulation of the capital, what finishes intervening with the agreement of what is to conquer and to extend right, fortifying, in such a way, the maintenance of the bourgeois societary project and creating, in the ideological field, a relation citizenship/help. Through of the competent speech of some specialists of the area of the education, the ruling class, with the support of the State, obtains to dominate the field psychological of the diligent classroom, assuming itself of the subjectivity and the objectivity of this. Thus, the vehicle of communication New School Magazine, for the psicology coercion, the manipulation of the public opinion and for the spreading of learning processes, contributes for the process of social reproduction, Through of the maintenance and acceptance of the social order. Ahead of this, we can affirm that, from referencial theoretician-methodological, the New School Magazine is characterized as ideological material efficient for the maintenance of the effective social order, syntonizing itself with the history of the exercise of hegemony of determined social classrooms that if they have used of different strategies to conserve, to legitimize and to extend its ballast of being able.